Pengaruh Resesi Ekonomi Global Terhadap Penjualan, Arus Kas, Dan Saham Pada Perusahaan Properti Di Indonesia - Anita Anita; Erni Hernawati; Clara Valencia (Jurnal Manajemen Riset Inovasi, 2023)
The purpose of this study is to determine the effect of the economic recession resulting from an increase in interest rates on sales, cash flows, and stock prices of property companies listed on the Indonesia Stock Exchange. This study examines the impact of the economic recession on sales, cash flow, and stock prices before the issue of the economic recession in the Q3 2022 period and after the recession issue appears in the Q4 2022 period. The measurement of cash flow and sales takes data from financial reports, while stock prices use the closing price of shares. This study uses a sample of property companies that have published their financial reports on the Indonesia Stock Exchange. The analysis of this study uses multiple linear regressions with the help of (Statistical Package for Social Science) SPSS 25. The results of this study indicate that (a) sales of property companies in Indonesia affect the issue of economic recession. (b) operating cash flows of property companies in Indonesia affect the issue of global economic recession (c) stock prices of property companies in Indonesia have no effect on the global economic recession.